LEXICAL PECULIARITIES OF IBANAG VARIETIES: The Case of Tuguegarao and Cabagan - Dolatre, Jasmin (International Journal of Arts, Sciences and Education, 2021)
The study investigated the lexical peculiarities between the Ibanag of Tuguegarao, Cagayan and the Ibanag of Cabagan, Isabela. Specifically, this study aimed at finding the difference between both dialects’ fillers, expressions, and lexemes. This study utilized a qualitative research design, particularly using the comparative-descriptive analysis approach. The study employed semi-structured interview to gather responses from the participants and non-participant observation on the dialect used by the participants in a conversation. Study revealed that there are indeed similar but also absolute and distinct features found from each of the dialects’ fillers, expressions, and lexemes. All the fillers given by the participants have an equivalent term and are also used in the opposite dialect. On expressions, some are totally similar in terms of spelling, usage in context, and pronunciation; for some, although the words are slightly different, they are still used for the same purpose in a conversation. On lexemes, the differences are categorized into the following: (1) added phoneme, (2) change of initial consonant sound, (3) change of final consonant sound, and (4) equivalent lexemes. The results of this study are beneficial not only to the speakers of the Ibanag dialect but also to the individuals who may have to deal and live with the Ibanag-speaking localities.